OPEN LEARNING: Communicating with the learner - Barkan, Murat; Özad, Bahire Efe (Tojet, 2004)
The present paper defines the key words of ‘Distance Teaching’(DT),‘Distance Education’(DE), and ‘Open (Distance) Learning’(ODL) to be followed by the exploration of the ‘Instructional Design’ (ID) concept, its’ principles and process and the operational steps to emphasize on the ever missing issue of the “communication with the learner”. Considering the fact that educational needs and requirements are loosing their ‘mass identity’ but becoming more individualized, communication with the learner becomes a more dominant fact in discussing the future strategies of education at a distance. The paper concludes with the suggestion that ‘Open Distance Learning (ODL)’ is the way ahead.
The file in this item is the publisher version (published version) of the article.
Keywords: Distance Education; Distance Teaching